Ethnoscience-Based Digital Comics to Improve Science Literacy of Fifth Grade Elementary School Students - Gusti Ayu Gita Cemara; I Nyoman Jampel; I Made Candiasa (Universitas Pendidikan Ganesha, 2026)
Low scientific literacy among elementary school students, particularly in learning food chain concepts that are abstract in nature, indicates that science and social studies instruction has not yet effectively connected scientific concepts with students’ real-life experiences and local cultural contexts. This condition highlights the need for innovative learning media that are not only visually engaging but also contextual and meaningful. This study aimed to analyze, evaluate, and examine the effectiveness of ethnoscience-based digital comics in improving the scientific literacy of fifth-grade elementary school students. The study employed a development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through expert reviews by material and media specialists, user assessments by teachers and students, classroom observations, and scientific literacy tests. Data analysis was conducted using descriptive statistics to determine the feasibility of the media, User Experience Questionnaire (UEQ) analysis to assess media usability, and inferential statistical analysis through a paired sample t-test, N-Gain calculation, and effect size to examine improvements in students’ scientific literacy. The results showed that the ethnoscience-based digital comic demonstrated a very high level of validity, was perceived as highly useful by users, and was proven to be effective in significantly improving students’ scientific literacy. These findings indicate that integrating ethnoscience into digital comics can concretize abstract science concepts and foster more contextual and meaningful learning experiences in elementary schools.